2005
DOI: 10.1007/s00439-005-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous missense mutation in FGF23 causes Familial Tumoral Calcinosis associated with disseminated visceral calcification

Abstract: Hyperphosphatemic Familial Tumoral Calcinosis (HFTC; MIM211900) is a rare autosomal recessive disorder characterized by the progressive deposition of calcified masses in cutaneous and subcutaneous tissues, associated with elevated circulating levels of phosphate. The disease was initially found to result from mutations in GALNT3 encoding a glycosyltransferase. However, more recently, the S71G missense mutation in FGF23, encoding a potent phosphaturic protein, was identified in two families. In the present repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 22 publications
1
63
0
2
Order By: Relevance
“…1b). Ophthalmological examination disclosed whitish ''salt-like'' deposits on the conjunctiva as previously described (Chefetz et al 2005). Of note, no cutaneous calcifications were observed.…”
Section: Clinical Findingssupporting
confidence: 71%
See 2 more Smart Citations
“…1b). Ophthalmological examination disclosed whitish ''salt-like'' deposits on the conjunctiva as previously described (Chefetz et al 2005). Of note, no cutaneous calcifications were observed.…”
Section: Clinical Findingssupporting
confidence: 71%
“…Although most patients display periarticular calcifications, other manifestations, such as visceral or mucosal involvement, are not invariably seen (Gal et al 1994;Topaz et al 2004;Chefetz et al 2005). Apart from severe joint disease, the present case was remarkable for prominent dental anomalies.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous molecular genetic analyses demonstrated that tumoral calcinosis can result from biallelic inactivating mutations in genes encoding FGF23 (1)(2)(3)(4) or the UDP-N-acetyl-α-D-galactosamine: polypeptide N-acetylgalactosaminyltransferase 3 (GALNT3) (5)(6)(7)(8). FGF23 is a hormone that promotes renal phosphate excretion by decreasing phosphate reabsorption in the proximal tubule and also reduces circulating 1,25(OH) 2 D by both decreasing biosynthesis and increasing metabolism of 1,25(OH) 2 D (9).…”
Section: Introductionmentioning
confidence: 99%
“…GALNT3 is a UDP-Nacetyl-␣-D-galactosamine:polypeptide N-acetylgalactosaminyl transferase that initiates mucin-like O-linked glycosylation of nascent proteins within the trans-Golgi network (4). Subsequently, we (22) and others (2,3,6) have shown that homozygous missense mutations in the fibroblast growth factor 23 (FGF23) gene cause TC; however, whether a common disease mechanism underlies these mutants is unknown.…”
mentioning
confidence: 99%